Interleukin-2 Production by Dendritic Cells and its Immuno-Regulatory Functions - Zelante, Teresa; Fric, Jan; Wong Yoke Wei, Alicia; Ricciardi-Castagnoli, Paola (Frontiers in Immunology, 2012)
Dendritic cells (DCs) are uniquely potent antigen presenting cells that acquire microbial products and prime adaptive immune responses against pathogens. Furthermore, DCs also play a key role in induction and maintenance of tolerance. Although numerous studies have assessed the diverse functions of DCs, many unanswered questions remain regarding the molecular mechanisms that DCs use to achieve immunoregulation. While not widely regarded as a significant provider of T cell growth factors, DCs have previously been identified as a potential source of IL-2 cytokine. Recent research indicates that microbes are the most effective stimuli to trigger IL-2 production in DCs by activating the calcineurin/NFAT signaling pathway. Herein we describe recent insights into the production and function of IL-2 cytokine and IL-2 receptor in DCs early after stimulation through pattern recognition receptors. These novel findings clarify how DCs fine-tune effector and regulatory responses by modulating IL-2 production in both tolerance and immunity.